Carbon aerogel for removal of oils and organic solvents spills - Chen, Geng (2016)
Water resource is limited and proper management has to be done so as to sustain the availability of fresh water. The demand for water is likely to increase due the increase in world population and industrial activities. However, current return of water back into the hydrosphere is hampered by persistent water pollution. The suitable way is to clean these contaminated water. There are many various water cleaning processes in which physical water treatments stand out as a fundamental method in the removal of contaminants. Many suitable materials such as zeolites and activated alumina are used in water cleaning. The production of these materials involved complex and expensive cost. Thus there is a need for a low cost and rich source material. Cellulose is found to be a suitable material to produce activated carbon. The production of activated carbon requires the use of carbonaceous precursors and subjecting it to pyrolysis procedures. This research explores the parameters involved in the pyrolysis of cellulose rich cotton to produce activated carbon, specifically the temperature and heating rate of pyrolysis. It is then established that increasing the temperature of pyrolysis from 200°C to 600°C will produce a better sorption of ethanol and vegetable oil with weight gain increase of about 2 times. However, a higher temperature at 800°C does not deliver any further advantage. This behaviour is attributed to the loss of functional groups that increase the hydrophobicity of the activated carbon In addition, heating rate of pyrolysis do not have any significant impact on the final end product. A slower heating rate of 10°C/min produces a better sorption capacity aerogel than at 15°C/min. The results of this research are useful in determining the suitable temperature and heating rate of pyrolysis for the production of activated carbon for various contaminants. Although cotton is proven to be a suitable precursor for activated carbon, other alternatives should be explored in terms of availability and market value. Nonetheless, the sorption capabilities of activated cotton had been proved effective in removal of organic solvent and oil which display a great potential in the field of water cleaning.